Felt with the Heart: A Review of WomenHeart.org. Issue 2 (3rd April 2021) - Phillips, Kat
Abstract: Heart disease is the leading cause of death among United States women, yet few resources focus on consumer health education, advocacy, and support. WomenHeart.org, the National Coalition for Women with Heart Disease, provides a space for all women living with or at risk of heart disease to connect, communicate, and advocate for and with each other. The national platform WomenHeart has built over two decades has rocketed them into a unique position of collaboration and action to educate on and fight for women's heart health in the United States. Their site, womenheart.org, provides clear, concise information on an easy to navigate platform. This site should be a first stop for anyone, from women new to their heart journey to seasoned medical practitioners and educators looking to provide additional information and support to their patients.